Highly water-stable bimetallic organic framework MgCu-MOF74 for inhibiting bacterial infection and promoting bone regeneration. (1st November 2022) - Liu, Jiamin; Tan, Yanni; Shen, Erdong; Liu, Bo; Tian, Yingtao; Liang, Luxin; Yan, Xinxin; Wu, Hong
Abstract: As a typical metal-organic framework (MOF), Mg-MOF74 can release biocompatible Mg 2+ when the framework is degraded, and it has the potential to be used as filler in the field of bone tissue engineering. However, Mg-MOF74 has poor stability in aqueous environment and limited antibacterial ability, which limit its further development and applications. In this work, MgCu-MOF74 particles with different Cu content were synthesized through a facile one-step hydrothermal method. The physicochemical properties and water stability of the synthesized powders were characterized. The osteogenic potential of the MgCu-MOF74 particles on human osteogenic sarcoma cells (SaOS-2) was evaluated. The hybrid MgCu-MOF74 exhibited favorable water stability. These results indicated that MgCu-MOF74 enhanced cellular viability, alkaline phosphatase levels, collagen (COL) synthesis and osteogenesis-related gene expression. Moreover, the samples doped with Cu 2+ were more sensitive to the acidic microenvironment produced by bacteria, and exhibited stronger antibacterial ability than Mg-MOF74. In conclusion, MgCu-MOF-74 with good water stability, osteogenic ability and antibacterial ability, which could be attributed to the doping of Cu 2+ . Hence, MgCu-MOF74 shows great potential as a novel medical bio-functional fillers for the treatment of bone defects.